2022
DOI: 10.3389/fphar.2022.944541
|View full text |Cite
|
Sign up to set email alerts
|

ATP indirectly stimulates hippocampal CA1 and CA3 pyramidal neurons via the activation of neighboring P2X7 receptor-bearing astrocytes and NG2 glial cells, respectively

Abstract: There is ongoing dispute on the question whether CNS neurons possess ATP-sensitive P2X7 receptors (Rs) or whether only non-neuronal cells bear this receptor-type and indirectly signal to the neighboring neurons. We genetically deleted P2X7Rs specifically in astrocytes, oligodendrocytes and microglia, and then recorded current responses in neurons to the prototypic agonist of this receptor, dibenzoyl-ATP (Bz-ATP). These experiments were made in brain slice preparations taken from the indicated variants of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…It is well-known that extracellular calcium in physiological concentrations acts as a negative allosteric modulator of P2X7R by reducing the affinity of receptors for orthosteric ligand agonists. 49 , 50 Thus, although a low Ca 2+ (0.5 mM)/0 Mg 2+ ACSF is routinely used to investigate the electrophysiological role of P2X7Rs in brain slices, 11 , 51 the physiological calcium concentration is typically around 1.3 mM and varies from 1.3 mM to 1.8 mM (normally below 1.8 mM) depending on arousal/sleep or other situations. 52 , 53 , 54 Therefore, in our study, we utilized both 1.3 mM Ca 2+ /2 mM Mg 2+ containing physiological ACSF and low Ca 2+ (0.5 mM)/0 Mg 2+ ACSF and found that BzATP was able to induce P2X7R-mediated response in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that extracellular calcium in physiological concentrations acts as a negative allosteric modulator of P2X7R by reducing the affinity of receptors for orthosteric ligand agonists. 49 , 50 Thus, although a low Ca 2+ (0.5 mM)/0 Mg 2+ ACSF is routinely used to investigate the electrophysiological role of P2X7Rs in brain slices, 11 , 51 the physiological calcium concentration is typically around 1.3 mM and varies from 1.3 mM to 1.8 mM (normally below 1.8 mM) depending on arousal/sleep or other situations. 52 , 53 , 54 Therefore, in our study, we utilized both 1.3 mM Ca 2+ /2 mM Mg 2+ containing physiological ACSF and low Ca 2+ (0.5 mM)/0 Mg 2+ ACSF and found that BzATP was able to induce P2X7R-mediated response in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…The P2X7 receptor was in fact first cloned from a rat brain tissue cDNA library, 21 and its expression and role in the CNS have been extensively researched. The expression of the P2X7 receptor in glial cells is widely accepted, whereas its expression in neurons has been a topic of heated debate, 50–52 which remains unsettled 53–55 . The P2X7 receptor serves an important mechanism mediating the communications between neurons and glia 56 .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the P2X7 receptor in glial cells is widely accepted, whereas its expression in neurons has been a topic of heated debate, 50 , 51 , 52 which remains unsettled. 53 , 54 , 55 The P2X7 receptor serves an important mechanism mediating the communications between neurons and glia. 56 The P2X7 receptor in microglia also acts as the PRR for ATP released from degenerating and stressed cells, and the ATP‐P2X7 receptor signaling axis plays a critical role in microglial activation and neuroinflammation in the pathogenesis and development of multiple neurodegenerative diseases and psychological disorders.…”
Section: Introductionmentioning
confidence: 99%